Integrating Local Culture-Based STEAM-PJBL to Enhance Competence in Fine Motor Skill Learning Design: A Development Study - Dwi Lyna Sari; Wembrayarli Wembrayarli; Siyyella Tika Nasution; Nesna Agustriana; Melia Eka Daryati (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2026)
The limited availability of learning media that integrate local cultural contexts within STEAM-based instruction remains a challenge in optimizing fine motor skill development in childhood education. This study aims to develop a Local Culture Oriented STEAM–Project-Based Learning (STEAM-PJBL) module and examine its feasibility, practicality, and effectiveness in enhancing fine motor skills among children aged 4–5 years. The study employed a Research and Development approach by adapting the Borg and Gall model into six stages: needs analysis, instructional design, prototype development, expert validation, product revision, and limited field testing. Participants included one content expert, one media expert, early childhood teachers, and eight children aged 4–5 years. Data were collected through observation, interviews, questionnaires, and pre- and post-tests of fine motor skills. The findings show high feasibility, with content validity of 91.6% and media validity of 89%. Teacher responses indicated high practicality at 92%. The module effectively improved children's fine motor skills, as shown by a significant increase in mean scores from 67.0 to 80.75 (p < 0.05). The novelty of this study lies in integrating local cultural contexts across all stages of STEAM-PJBL design, positioning fine motor development as a core learning outcome in early childhood education.